Strength of Materials / Elementary Theory and Problems: Part I - Timoshenko S (Robert E. Krieger Publishing Company, 1976)
Tension and Compression within the Elastic Limit, Analysis of Stress and Strain, Bending Moment and Shearing Force, Stresses in Laterally Loaded Symmetrical Beams, Deflection of Laterally Loaded Symmetrical Beams, Statically Indeterminate Problems in Bending, Symmetrical Beams of Variable Cross Section - Beams of Two Materials, Bending of Beams in a Plane Which is not a Plane of Symmetry, Combined Bending and Axial Load - Theory of Columns, Torsion and Combined Bending and Torsion, Strain Energy and Impact, Curved Bars, Appendices, Author and Subject Index.
Tension and Compression within the Elastic Limit, Analysis of Stress and Strain, Bending Moment and Shearing Force, Stresses in Laterally Loaded Symmetrical Beams, Deflection of Laterally Loaded Symmetrical Beams, Statically Indeterminate Problems in Bending, Symmetrical Beams of Variable Cross Section - Beams of Two Materials, Bending of Beams in a Plane Which is not a Plane of Symmetry, Combined Bending and Axial Load - Theory of Columns, Torsion and Combined Bending and Torsion, Strain Energy and Impact, Curved Bars, Appendices, Author and Subject Index.